Testing the Corrosion Rate of Prestressed Concrete Beams Under Variable Temperature and Humidity Conditions - Szweda, Zofia; Krak, Michał; Czerniak, Szymon; Skórkowski, Artur; Małek, Jacek; Sikorski, Jakub; Trojan, Jakub; Konečný, Petr; Vacek, Miroslav; Marek, Jakub (Materials (Basel, Switzerland), 2025)
To date, many studies can be found in the literature attempting to explain the effects of temperature and humidity on the rate of corrosion processes. However, it is difficult to analyze the results of these studies and draw unambiguous conclusions due to the different test conditions as well as different electrochemical test methods for corrosion rates. Most of these studies concern concrete reinforced with ordinary steel. However, there is a lack of research and analysis conducted on prestressed elements. The purpose of this study was to evaluate the effect of temperature and humidity changes on the development of corrosion processes in prestressed concrete beams. Tests were performed both under conditions of increasing temperature and humidity, which were reproduced in a climatic chamber, as well as in an environment exposed to chloride ions. The process of migration of chloride ions into the concrete was accelerated by the application of an electric field. In addition, selected beams were subjected to prolonged loading to sustain the induced scratching. Corrosion rate tests were carried out using the non-destructive linear polarization method (LPR). Strength tests of the beams were also carried out, as well as displacement and deformation measurements using the Aramis system's digital image correlation technique. The beams without chloride addition had a fairly stable low level of corrosion current density throughout the test period, indicating the passive state of the reinforcement, regardless of the environment in which they were placed and the additional loading. In an environment with a humidity of 30% and a temperature of 20 °C, the corrosion current density increment was much faster than for beams with chloride additives in an environment with a humidity of 90% and a temperature of 30 °C. A smaller increase in corrosion current density could be observed in beams that were scratched, compared to non-scratched beams. The results of the strength tests indicated that in beams subjected to accelerated migration of chloride ions, the deflection at scratching was significantly lower than in beams without chloride addition. Also in these beams, milder strains were registered on the surface of the elements at the time of scratching.
Keywords: prestressed concrete beams; long-term loading; humidity rise; strength of beams; chloride migration; temperature rise; scratching; digital image correlation; LPR method; corrosion rate